2017
DOI: 10.1002/jsfa.8339
|View full text |Cite
|
Sign up to set email alerts
|

Influence of biofilm surface layer protein A (BslA) on the gel structure of myofibril protein from chicken breast

Abstract: Addition of 0.01 g kg BslA significantly improved the water holding capacity and rheological properties of MP by developing non-disulfide covalent bonds. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…reported that the addition of soy protein isolate strengthened gel structures of MP gels. Feng et al 47 . also reported that the addition of biofilm surface layer protein A (BslA) could promote a uniform pore network of MP and may modify the gel matrix in the gel process.…”
Section: Resultsmentioning
confidence: 99%
“…reported that the addition of soy protein isolate strengthened gel structures of MP gels. Feng et al 47 . also reported that the addition of biofilm surface layer protein A (BslA) could promote a uniform pore network of MP and may modify the gel matrix in the gel process.…”
Section: Resultsmentioning
confidence: 99%
“…Dynamic rheological studies were performed as described by Ullah et al [27] using a rotary rheometer (DSR200, Rheometric Scientific, Newcastle, DE, USA) equipped with a 40 mm parallel plate geometry. The raw batter samples were placed between the flat parallel plates (0.5 mm gap).…”
Section: Dynamic Rheological Measurementmentioning
confidence: 99%
“…Chen et al suggested that a homogeneous and delicate network structure could better bind water into the gel system and enhance its water retention and other gel properties [ 45 ]. Ullah et al reported that moderate amounts of natto protein could improve the chicken muscle fiber protein gel microstructure and also reduced the cooking loss [ 46 ]. Ji et al, also reported that konjac glucans helped Alaskan pollock minced fish to form more compact and homogeneous mixed gels [ 47 ] that combined to promote interactions between proteins, water and other molecules to produce more cross-linking into proteins with larger molecular weights and, finally, a rigid three-dimensional network microstructure.…”
Section: Resultsmentioning
confidence: 99%